2020
DOI: 10.1002/mnfr.201901151
|View full text |Cite|
|
Sign up to set email alerts
|

Low AMY1 Copy Number Is Cross‐Sectionally Associated to an Inflammation‐Related Lipidomics Signature in Overweight and Obese Individuals

Abstract: Scope Reduced amylase 1 (AMY1) copy numbers are associated with obesity, insulin resistance, and inflammation. Although mechanisms linking AMY1 copy number with metabolic disorders are poorly understood, recent findings suggest that lipids play a key role. Methods and results Plasma lipidomic signatures associated with AMY1 copy number are explored in 57 non‐diabetic overweight/obese subjects aged 18–60. Serum amylase and inflammatory cytokines levels are also measured. AMY1 copy number is strongly associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 51 publications
0
8
1
Order By: Relevance
“…The median of AMY1 gene CN was 7, which is like the one reported recently 15,17 . However, other studies previously reported a median of 4 7,14,27 . We have no explanation for this large difference in median AMY1 gene CN, but the different ethnicities studied, or the techniques used to estimate the CNV might play a role.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…The median of AMY1 gene CN was 7, which is like the one reported recently 15,17 . However, other studies previously reported a median of 4 7,14,27 . We have no explanation for this large difference in median AMY1 gene CN, but the different ethnicities studied, or the techniques used to estimate the CNV might play a role.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have investigated the relationship between AMY1 gene CN and predisposition to metabolic disorders, including obesity, T2D and insulin resistance, in both children and adults. However, contradicting results were reported 7,[12][13][14][15]18,19,[21][22][23][24][25][32][33][34] .The reported discrepancies remain unexplained, and possible reasons include the different techniques used to estimate the AMY1 gene CN 35 as well as the different ethnicities 21,36 www.nature.com/scientificreports/ and age 37 of the populations studied. The distribution of AMY1 gene CN in our study sample (2-20 copies) is comparable to what was reported previously across modern human populations 38 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…After adjusting for age, sex, fat mass, and dietary factors, associations between AMY1A copy numbers and inflammation markers (except MCP‐1) remained significant. In addition, in the same cohort, low AMY1A copy numbers have been associated with a lipidomic signature previously linked to obesity and chronic low‐grade inflammation 51 …”
Section: Amy1a and Cardiovascular Risk Factors And Markers Of Inflammationmentioning
confidence: 80%
“…In addition, in the same cohort, low AMY1A copy numbers have been associated with a lipidomic signature previously linked to obesity and chronic low-grade inflammation. 51 The second study was a cohort study that used 80 Caucasian participants from the previously mentioned ProFiMet population and found that individuals with high AMY1A copy numbers had statistically higher serum adiponectin (p = 0.026) and HDL cholesterol. 23 There were no statistically significant associations between AMY1A copy numbers and any other serum lipid or inflammatory markers measured including IL-10 and CRP, among others.…”
Section: Observational Studies Examining Amy1a and Cardiovascular Risk And Inflammationmentioning
confidence: 99%